2014
DOI: 10.7866/hpe-rpe.14.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Some New Results on the Estimation of Structural Budget Balance for Spain

Abstract: SummaryThe recession that started in 2008 caused a sharp deterioration of the budget balance of Spain. This decline was not fully anticipated by the structural budget balance due to some methodology limitations. In this article, we calculate an alternative structural balance for Spain in the years prior to the subprime crisis that includes residential investment as an explanatory variable. This estimate shows that by 2004 the Spanish fiscal situation was not as strong as presumed. This fragility was hidden by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
2
0
5
Order By: Relevance
“…Sin embargo, como se ha visto a partir de la crisis de 2008, este indicador no es satisfactorio a la hora de identificar los ingresos producto de la revalorización de activos. Para ello es de suma utilidad desarrollar un indicador estructural que sí considere estos efectos, como el desarrollado por Zack et al, (2014) 7 .…”
Section: El Resultado Fiscalunclassified
See 2 more Smart Citations
“…Sin embargo, como se ha visto a partir de la crisis de 2008, este indicador no es satisfactorio a la hora de identificar los ingresos producto de la revalorización de activos. Para ello es de suma utilidad desarrollar un indicador estructural que sí considere estos efectos, como el desarrollado por Zack et al, (2014) 7 .…”
Section: El Resultado Fiscalunclassified
“…A cambio, se hará uso del RFE para España estimado por Zack et al (2014). Como se puede ver en el cuadro 1, este se diferencia significativamente del RFE estimado por la Comisión Europea básicamente por tener en consideración los ingresos públicos extraordinarios producto de la burbuja inmobiliaria y del boom en la construcción.…”
Section: El Caso De España Previo a 2008: Un Ejercicio De Aplicaciónunclassified
See 1 more Smart Citation
“…In this respect, since the beginning of the crisis, there was a tendency towards over-optimism in Spain's official macroeconomic 5 The significant increase in public revenues during the expansion was not fully of a structural nature. Rather, some studies identified a substantial temporary component (see Zack et al (2014) Note: Due to data availability, the breakdown of social protection in Figure 4b is based on the European system of national and regional accounts 1995, ESA95, instead of the ESA 2010 standard on which Figure 4a projections, which carried over to government revenue forecasts. These are features shared with many other OECD governments.…”
Section: Fiscal Stance Before the Crisismentioning
confidence: 99%
“…Rather, some studies identified a substantial temporary component (see Zack et al. () and the references quoted therein).…”
mentioning
confidence: 99%